Systemic administration of curcumin or piperine enhances the periodontal repair: a preliminary study in rats - Guimaraes-Stabili, Morgana R. [UNESP]; de Aquino, Sabrina Garcia; de Almeida Curylofo, Fabiana [UNESP]; Tasso, Camilla Olga [UNESP]; Rocha, Fernanda Regina Godoy [UNESP]; de Medeiros, Marcell Costa [UNESP]; de Pizzol, José Paulo [UNESP]; Cerri, Paulo Sérgio [UNESP]; Romito, Giuseppe Alexandre; Rossa, Carlos [UNESP] (Springer Nature, 2019)
Objectives: Studies have documented the anti-inflammatory effects of spices, which may be related to treatment of chronic diseases. The purpose of this study was to evaluate the influence of curcumin and piperine and their association on experimental periodontal repair in rats. Materials and methods: Periodontitis was induced via the installation of a ligature around the first molar. After 15 days, the ligatures were removed, and the rats were separated into groups (12 animals per group): (i) curcumin, (ii) piperine, (iii) curcumin+piperine, (iv) corn oil vehicle, and (v) control group (animals had ligature-induced periodontitis but were not treated). The compounds were administered daily, for 15 days by oral gavage. Animals were euthanized at 5 and 15 days, and hemimaxillae and gingival tissues were harvested. Bone repair was assessed by μCT (microcomputer tomography). Histological sections were stained with hematoxylin/eosin (H/E) for the assessment of cellular infiltrate or picrosirius red for quantification of collagen content, and subjected to immunohistochemistry for detecting NF-ĸB. Gingival tissues were used to evaluate levels of TGF-β and IL-10 (ELISA). Results: Curcumin and piperine increased the TGF-β level, significantly improved the collagen repair, and decreased the cellularity and activation of NF-ĸB in the periodontal tissues, but only curcumin caused a significant increase in early bone repair. Conclusion: Curcumin and piperine promoted a substantive effect on tissue repair; however, there was not synergistic effect of compounds administered in combination. Clinical relevance: Curcumin and piperine stimulates the tissue repair and may be potential candidates for the treatment of periodontal disease.
Keywords: Curcumin; Periodontal disease; Piperine; Rats; Repair